국내 HR Analytics 연구에서 활용한 데이터와 분석방법에 대한 체계적문헌고찰 - 정재삼(Jaesam Chung); 조예인(Yein Cho); 양하영(Hayeong Yang); 진명화(Myunghwa Jin); 박효성(Hyosung Park); 이재영(Jae Young Lee) (한국콘텐츠학회 논문지, 22(9), 2022)
The purpose of this study was to explore the various data and methods employed by HR analytics studies. The researchers selected 78 KCI-indexed empirical articles on HR analytics and categorized them using the Employee Life Cycle framework. This yielded several important findings. First, employee retention has been the most common subject of extant studies, followed by performance management. Second, HR analytics studies have used a variety of data (structured and unstructured) according to their research questions, and the data sources have ranged from organizations' internal systems to national databases. Third, most domestic HR analytics studies have been descriptive and diagnostic, whereas predictive and prescriptive studies have been rare. These results have important theoretical and practical implications for future HR analytics research. 본 연구는 국내 HR Analytics 연구에서 활용한 데이터와 분석방법을 탐색하여 향후 연구를 위한 기초자료를 제공하고 HR Analytics 연구 현황을 밝히는 것을 목적으로 한다. 이를 위하여 체계적 문헌고찰 방법을 활용하여 국내 KCI 등재 학술지에 수록된 실증연구 논문 78편을 선정하였고 해당 논문을 근로자 생애주기에 따라 분류하여 검토하였다. 문헌고찰 결과 다음과 같은 결과를 얻을 수 있었다. 첫째, 근로자 생애주기에 따른 HR Analytics 연구 동향을 살펴본 결과, 선행연구에서는 구성원의 유지(retention)와 관련한 연구가 가장 많았고 성과 관리에 대한 연구가 그 뒤를 이었다. 둘째, HR Analytics 연구에서 사용한 데이터를 살펴본 결과 각 연구는 해당 연구문제에 따라 다양한 데이터(정형, 비정형)를 활용하고 있었으며 데이터 출처 또한 조직내부 시스템부터 국가 통계 DB까지 매우 다양한 것으로 확인하였다. 셋째, 문헌고찰 결과 국내 HR Analytics 연구는 기술적, 진단적 분석이 가장 많으며, 예측 및 처방과 관련한 연구는 미미한 수준임을 알 수 있었다.